1994
DOI: 10.1515/zna-1994-1103
|View full text |Cite
|
Sign up to set email alerts
|

14N Quadrupole Relaxation of DMF and DMF-d7 in DMSO at Infinite Dilution

Abstract: The 14N quadrupole relaxation time in pure D M F is by 9% longer than in pure DMF-d7, showing the dependence of the reorientational molecular motion on the square root of the moment of inertia. But for traces of DM F and DMF-d7 in DMSO, the 14N quadrupole relaxation time tends to obey the "square-root-of-the-reduced-mass law", as expected from the kinetic theory of dense fluids. The vanishing of the moment-of-inertia effect on the intramolecular nuclear quadrupole relaxation is discussed in terms of molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Dynamic isotope effects have been reported for several isotopomer couples in molecular liquids [13][14][15][16][17][18]. Substantially the isotopic effect consists in the effect produced on the transport properties of a fluid by the change of the molecular mass and is quantitatively expressed by the so called 'square-root mass law' [15], as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic isotope effects have been reported for several isotopomer couples in molecular liquids [13][14][15][16][17][18]. Substantially the isotopic effect consists in the effect produced on the transport properties of a fluid by the change of the molecular mass and is quantitatively expressed by the so called 'square-root mass law' [15], as follows:…”
Section: Discussionmentioning
confidence: 99%
“…To date, the experiments on this effect have been directed to measurements of self-diffusion coefficient (D), shear viscosity coefficient (η) and rotational correlation times derived by NMR experiments [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Following the literature, we notice that a number of NMR studies on pure liquid DMF and DMF-d7, as well as on some of their mixtures, have been reported up to now. M. Holz et al 33,38,39 published a series of experimental studies on this system by using the 14 N and 17 O NMR quadrupole relaxation technique. In Table VII we list the NMR experimental reorientational time 2 ϭ2.4 ps for liquid DMF at 298 K. From the above results we see that the agreement between NMR 2 data and MD simulation with CS2 potential is quite satisfactory.…”
Section: ͑8͒mentioning
confidence: 99%
“…--------------- Ισοδύναμος προς την ανωτέρω περιγραφή είναι και η περιγραφή ακολουθώντας φορμαλισμό "Heisenberg" κατά τον οποίο η χρονική εξάρτηση του συστήματος περιγράφεται μέσω τελεστών [13]. ---------------------ω Πυκνότητα (ρ) [25][26][27] Πρόσθετο Μοριακό Όγκο (Ve) [28] Μοριακή θερμότητα εξάτμισης (ΔΗν) [29][30][31][32] Ελεύθερη ενέργεια κατά Gibbs (AGf) [32] Μοριακή θερμότητα καύσης (AHc) [32] Γραμμομοριακές Θερμοχωρητικότητες (Cp, Cv) [32] Δείκτη διάθλασης (nD) [32] Συντελεστή επιφανειακής τάσης (γ) [32] Τάση ατμών (ρ) [32] Συντελεστής ιξώδους (η) [33][34][35][36] καθώς και μετρήσεις άλλων ιδιοτήτων με τις παρακάτω φασματοσκοπικές μεθόδους:…”
Section: φαινόμενα μεταφοράςunclassified
“…Τα αποτελέσματα παρατίθενται στον Πίνακα 6.9. Πίνακας 6.9 : Οι συντελεστές διάχυσης των μορίων DMSO(-d0) και DMSO(-df) από τις προσομοιώσεις (MD) και οι αντίστοιχες διαθέσιμες πειραματικές τιμές[33,34] Οι συντελεστές διάχυσης που υπολογίζονται και για τα δύο μοριακά συστήματα με την MD συγκρινόμενοι με τις αντίστοιχες πειραματικές τιμές[33,34] παρουσιάζουν πολύ καλή συμφωνία. Το γεγονός αυτό ενισχύει το συμπέρασμα ότι το προτεινόμενο δυναμικό είναι αξιόπιστο στο να αναπαράγει μια σειρά φυσι κοχημικών ιδιοτήτων με ικανοποιητική ακρίβεια.Από τις τιμές των συντελεστών διάχυσης των δύο συστημάτων που συνοψίζονται στον Πίνακα 6.9 φαί νεται ότι ο συντελεστής διάχυσης των μορίων του DMSO(-do) είναι μεγαλύτερος από τον αντίστοιχο συ ντελεστή των μορίων του DMSO(-d6) σε ίδιες θερμοδυναμικές καταστάσεις.…”
unclassified